How overconfidence and mental accounting influence investments? The moderating role of financial literacy - Budiman, Johny; Yodiputra, Jason; Candy, Candy; Agustin, Isnaini Nuzula (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This research aims to investigate the influence of behavioral finance on stock investment decision-making in Indonesia, considering both rational and irrational behaviors. Key behavioral finance factors, including overconfidence, herding bias, mental accounting, and loss aversion, are examined to understand their impact on stock investment decisions, the financial literacy as moderating variables has been added to the model. A self-administered questionnaires were distributed to 391 active trading stock investor in Indonesia. Using Partial Least Squares method, the results shows that loss aversion and overconfidence negatively influence the investment decision. Further, the analysis confirmed the role of financial literacy as moderating variable for mental accounting and overconfidence. It is also consistent with the notion that financial literacy at least in terms of mental accounting biases under some conditions might actually reinforce certain specific cognitive shortcuts. This study’s results suggest policymakers and financial educators should work to increase investors’ literacy about finance, as well as their ability to identify biases they hold which could be used against them when making investment decisions.